Growth, Efficiency of Feed Utilization and Economics of Different Rearing Periods of Turkeys Mukesh Karki - Karki, Mukesh (Nepal Agriculture Research Journal, 2010)
The present study on body weight and feed efficiency for growth was carried out on 112 turkey poults from day of hatch to 28 weeks of age during May to November 2002 at Poultry Research Unit of Regional Agricultural Research Station (RARS)-Parwanipur. Layer starter ration supplemented with 6% fish meal + 0.3% lysine + 0.125% methonine was fed up to 8 weeks of age, then after layer finisher diet was fed. The body weight, feed consumption was observed at 4 weekly interval and feed efficiency and economics of rearing period in terms of income over feed and poults cost was calculated. Significant increase in body weight was recorded up to 28 weeks in male and 20 weeks in female. Male turkey had significantly higher body weight than that of female in all ages. Feed efficiency is best at earlier age but up to 16 weeks it is 3.77 for male after that it detoriates progressively. Male turkey exhibited better feed efficiency than that of female for all weeks. Significantly higher return per bird was obtained from male than that of female in all age. The profit per bird for both male and female was found maximum in 16 weeks of rearing, followed by 20 weeks and 24 weeks. Therefore, instead of waiting for highest body weight, it is better to sell turkey at 16 to 20 weeks of age to take maximum advantage of higher weight gain, higher efficiency of feed utilization and higher profit. Key words: Economics; feed utilization; growth; rearing period; turkey DOI: 10.3126/narj.v6i0.3369 Nepal Agriculture Research Journal Vol.6 2005 pp.84-88